Hole fertilization in the root zone facilitates maize yield and nitrogen utilization by mitigating potential N loss and improving mineral N accumulation - Wen-xuan SHI; Qian ZHANG; Lan-tao LI; Jin-fang TAN; Ruo-han XIE; Yi-lun WANG (Journal of Integrative Agriculture)
Reducing environmental impacts and improving N utilization are critical to ensuring food security in China. Although root-zone fertilization has been considered an effective strategy to improve nitrogen use efficiency (NUE), the effect of controlled-release urea (CRU) applied in conjunction with normal urea in this mode is unclear. Therefore, a 3-year field experiment was conducted using a no-N-added as a control and two fertilization modes (FF, furrow fertilization by manual trenching, i.e., farmer fertilizer practice; HF: root-zone hole fertilization by point broadcast manually) at 210 kg N ha–1 (controlled-release:normal fertilizer=5:5), along with a 1-year in-situ microplot experiment. Maize yield, NUE and N loss were investigated under different fertilization modes. The results showed that compared with FF, HF improved the average yield and N recovery efficiency by 8.5 and 22.3% over three years, respectively. HF had a greater potential for application than FF treatment, which led to increases in dry matter accumulation, total N uptake, SPAD value and LAI. In addition, HF remarkably enhanced the accumulation of 15N derived from fertilizer by 17.2% compared with FF, which in turn reduced the potential loss of 15N by 43.8%. HF increased the accumulation of N in the tillage layer of soils at harvest for potential use in the subsequent season relative to FF. Hence, HF could match the N requirement of summer maize, sustain yield, improve NUE and reduce environmental N loss simultaneously. Overall, root-zone hole fertilization with blended CRU and normal urea can represent an effective and promising practice to achieve environmental integrity and food security on the North China Plain, which deserves further application and investigation.